Light-Guided Surface Engineering for Biomedical Applications - Jayagopal, Ashwath (2008)
Free radical species generated through fluorescence photobleaching have been reported to effectively couple a water-soluble species to surfaces containing electron-rich sites (1). In this report, we expand upon this strategy to control the patterned attachment of antibodies and peptides to surfaces for biosensing and tissue engineering applications. In the first application, we compare hydrophobic attachment and photobleaching methods to immobilize FITC-labeled anti-M13K07 bacteriophage antibodies to the SiO(2) layer of a differential capacitive biosensor and to the polyester filament of a feedback-controlled filament array. On both surfaces, antibody attachment and function were superior to the previously employed hydrophobic attachment. Furthermore, a laser scanning confocal microscope could be used for automated, software-guided photoattachment chemistry. In a second application, the cell-adhesion peptide RGDS was site-specifically photocoupled to glass coated with fluorescein-conjugated poly(ethylene glycol). RGDS attachment and bioactivity were characterized by a fibroblast adhesion assay. Cell adhesion was limited to sites of RGDS photocoupling. These examples illustrate that fluorophore-based photopatterning can be achieved by both solution-phase fluorophores or surface-adhered fluorophores. The coupling preserves the bioactivity of the patterned species, is amenable to a variety of surfaces, and is readily accessible to laboratories with fluorescence imaging equipment. The flexibility offered by visible light patterning will likely have many useful applications in bioscreening and tissue engineering where the controlled placement of biomolecules and cells is critical, and should be considered as an alternative to chemical coupling methods.